2021
DOI: 10.3389/fgene.2020.548407
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Validation of Major Quantitative Trait Loci for Resistance to Northern Corn Leaf Blight Along With the Determination of the Relationship Between Resistances to Multiple Foliar Pathogens of Maize (Zea mays L.)

Abstract: Among various foliar diseases affecting maize yields worldwide, northern corn leaf blight (NCLB) is economically important. The genetics of resistance was worked out to be quantitative in nature thereby suggesting the need for the detection of quantitative trait loci (QTL) to initiate effective marker-aided breeding strategies. From the cross CML153 (susceptible) × SKV50 (resistant), 344 F2:3 progenies were derived and screened for their reaction to NCLB during the rainy season of 2013 and 2014. The identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Scoring for MLB response was done once, 35 days after the artificial inoculation following rating scale of 1–9 (Hooda et al, 2018). One time disease scoring of population for mapping foliar disease‐resistant QTLs in maize has also been adopted previously by Zwonitzer et al (2010) and Ranganatha et al (2021). The disease rating was then converted into percent disease index (PDI) by using the formula given below:PDIgoodbreak=][)(Sum0.25emof0.25emall0.25emthe numerical ratinggoodbreak×100/)(Total number of observationgoodbreak×maximum rating.…”
Section: Methodsmentioning
confidence: 99%
“…Scoring for MLB response was done once, 35 days after the artificial inoculation following rating scale of 1–9 (Hooda et al, 2018). One time disease scoring of population for mapping foliar disease‐resistant QTLs in maize has also been adopted previously by Zwonitzer et al (2010) and Ranganatha et al (2021). The disease rating was then converted into percent disease index (PDI) by using the formula given below:PDIgoodbreak=][)(Sum0.25emof0.25emall0.25emthe numerical ratinggoodbreak×100/)(Total number of observationgoodbreak×maximum rating.…”
Section: Methodsmentioning
confidence: 99%
“…Moderate to high genomic prediction accuracies were observed between 0.58 and 0.83 based on population and continent. Recently, Ranganatha et al [130] evaluated CML153 (susceptible) and SKV50 (resistant) based 344 F 2:3 population for NLCB resistance and identified two major QTLs namely qNCLB-8-2 (phenotypic variation of 16.34%) and qNCLB-5 (phenotypic variation of 10.24%). Nevertheless, numerous QTLs have been identified in different populations by different research groups, but integrating the data of all the QTLs is an efficient approach to identify the consensus or stable regions harbouring multiple QTLs.…”
Section: Variability and Population Structure Of E Turcicummentioning
confidence: 99%
“…Wang et al ( 2018 ) identified 11 QTLs from cross Ye478 × Qi319, and identified qNCLB7.02 as a consistent major resistant locus across multiple environments, with PVE ranging from 10.11% to 15.29%. Ranganatha et al ( 2020 ) detected five NLB resistant QTLs with PVE ranging from 1.64% to 16.34% in 344 families of an F 2:3 population derived from cross CML153 × SKV50. Ding et al ( 2015 ) conducted GWAS for mean rating, high rating and area under the disease progress curve using single-marker and haplotype-based associations in a population of 999 maize inbred lines, and identified multiple SNPs associated with NLB across all 10 maize chromosomes.…”
Section: Introductionmentioning
confidence: 99%